CORRELATION OF SURFACE ROUGHNESS AND FRICTION RESISTANCE IN ORTHODONTICS - Aditya, Grahita; Santoso, Oedijani; Suromo, Lisyani; Nugraha, Reeza Maulana (Odonto : Dental Journal, 2022)
Background: The orthodontic bracket transmit significant force from orthodontic wire to the teeth. Metal ions from the bracket may undergo biodegradation due to corrosion and create micro pit on the surface which increase friction resistance. Friction resistance between the archwire and the bracket may effect tooth movement and cause loss of anchorage. This study determine the correlation between surface roughness and friction resistance in orthodontic Roth brackets.Method: Seventeen brackets were prepared from previous study and were analyzed using SEM-EDX (Phenom Pro X) to measure surface roughness. Friction resistance were measured using universal testing machine. Data were analyzed using Spearman correlation.Result: Significant correlation were found between surface roughness and friction resistance on orthodontic brackets (p<0.05). The relationship is strongly correlated and directly proportional, with a positive coefficient value of 0.587. Conclusion: The conclusion of the research showed that there was a significant correlation between surface roughness and friction resistance of orthodontic brackets.